A produção científica brasileira sobre atividades circenses e sua relação com a educação física escolar - Lima, Ana Carolina Cândido e [UNESP] (2015)
As an ancient knowledge, the circus possesses a wealthy cultural and motor content being able to benefit the development through more transformative and critical learning process. Considering the circus activities as part of the body culture, your presence at educational institutions justified itself once to pass on the cultural legacy it is one of these institution's duties. The Law of Directives and National Educational Bases and the National Curriculum Parameters are documents responsible to arrange and bring forward what it will be transmitted to educational institutions all over the country, therefore this documents complemented by the curriculum proposed of each State. Of 27 brazilian states, 4 presents circus activities in their proposal, indicating that circus activities although timid are beginning to attend the brazilian school range. This study based itself in a documentar research type, related to studies about Circus Activities and School Physical Education in witch was found 110 documents generates by the for key words, selecting 44 references, dealing specifically with the Circus Activities/Circus and School Physical Education theme, being possible to observe that circus activities in Brazil come across the margino f Brazilian education and that this knowledge still being too little broadcasted, researched and worked